Ride comfort enhancement for passenger vehicles using the structure-immittance approach. Issue 4 (3rd April 2021) - Zhang, S. Y.; Zhu, M.; Li, Y.; Jiang, J. Z.; Ficca, R.; Czechowicz, M.; Neilson, R.; Neild, S.A.; Herrmann, G.
Abstract : This paper presents a novel approach to identify inerter-based suspension struts, which can provide significant performance enhancement for passenger vehicles. The inerter has been used on Formula 1 racing cars, and several beneficial devices incorporating inerters have also been identified for ride comfort enhancement. However, previous investigations either were limited to simple network configurations with moderate performance improvement, or resulted in complicated configurations with a large number of elements which are impractical for real-life applications. In addition, some important practical performance constraints have not been taken into consideration, such as high-frequency dynamic stiffness which influences the NVH performance, and frequency content consideration of the sprung mass acceleration which more directly relates to passenger perception. In this paper, a quarter-car model including top mount is studied, with the performance of a conventional suspension strut presented as baseline. The structure-immittance approach, which can cover all networks with pre-determined numbers of each element type, is adopted for the identification of the optimal suspension configurations. Several configurations with up to a 14.7 % performance improvement are identified with all other practical performance indices to be no worse than the baseline. The suspension devices proposed in previous works are also considered for a sake of comparison, demonstrating significant advantages of the structure-immittance approach. Subsequently, a sensitivity analysis against the sprung and unsprung mass changes is carried out, which represents cargo and tyre weight variations, respectively. Time domain response and other reality checks are then conducted for the out-performing configurations, which reconfirm the ride comfort enhancement and ensure no unexpected behaviour occurs.